Vibration testing and structural analysis of chip scale atomic clock - Yap, Marianne Xinyi (2017)
This project is a study done to evaluate the clocking performance of a Chip Scale Atomic Clock (CSAC) under Static and Vibrational situations. 3 main tests were carried out on the CSAC- Static Test, Dynamic Test and Simulation.